Predisposing, Enabling and Reinforcing Factors of the Utilization of VCT by Men Who Have Sex with Men (MSM) - Risanita Diah Fatmala (Universitas Airlangga, 2016)
Men who have sex with men (MSM) have a high risk of being infected with the Human Immunodeficiency Virus (HIV) due to frequent changes in partners and anal intercourse. New cases of HIV and Acquired Immunodeficiency Syndrome (AIDS) in MSM in Indonesia have increased significantly compared to the previous year. Voluntary Counseling and Testing (VCT) is one of HIV and AIDS prevention and control strategies which is considered quite effective. This study aims to determine the factors associated with the utilization of VCT by MSM. This study uses a qualitative method. Informants were taken by snowball sampling on 9 MSM members of the IGAMA Malang Foundation. Data were collected by conducting in-depth interviews, analyzed descriptively, and presented in narrative form. The results showed that most informants had very good knowledge about HIV and AIDS and VCT. This raises awareness of the risk factors for being infected with the HIV virus, but access to VCT services is still constrained by service schedules which are mostly during active working hours. Encouragement to access VCT was obtained from friends in the community (field officers). There is no stigma and discrimination against MSM by health care workers. Attitudes and behavior of health workers make them comfortable because they are already close enough and familiar with informants. It was concluded that factors related to the utilization of VCT by MSM included knowledge, perceptions, information, availability of facilities and facilities, support from friends and attitudes, or behavior of health workers. It is recommended that VCT services can also be done on weekends or not on active workdays.